Sistem Manajemen Inventori Komputer Menggunakan Near Field Communication Berbasis Android Studi Kasus di STIE Pelita Indonesia Pekanbaru - Muhammad Luthfi Hamzah; Astri Ayu Purwati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2017)
Higher education is an institution that is heavily influenced by technological advances,especially in the field of computer technology. The purpose of this study is to create a computer inventory management system in higher education which is previously using manuals system become technology based system in order to work more effective and efficient. The research method used is design of inventory tracking system application using NFC android based. The results showed that by using Inventory Tracking Systems model is more effectiveand efficient to identify any inventory information in the computer lab STIE Pelita Indonesia Keywords :Inventory Tracking, RFID, Near Field Communication, NFC